Body Size and Composition of U.S. National Team Skiers and Snowboarders - Sands, William A; McNeal, Jeni R; Bullock, Joshua; Schiller, Tschana; Deck, Houston; Penitente, Gabriella; Donti, Olyvia; Bogdanis, Gregory C (Journal of Sports Research, 2021)
Athlete profiles have been a reliable means of characterizing athlete groups and individuals. Anthropometric data have been collected uniformly from 2010 to 2015 by U.S. Ski and Snowboard personnel and archived for analyses. These data involved 834 anthropometric tests on 234 individual athletes. The purpose this study was to understand these elite competitors' size, shape, and body composition. Competitors are categorized by their events: Alpine Skiing, Free Ski, FreeStyle, and Snowboard, with each event having subdisciplines. Missing data and the relative recency of some events and subdisciplines led to four athlete groups' analyses: alpine skiing, aerial skiing, moguls skiing, and snowboard halfpipe. ISAK trained anthropometrists and methods assessed the athletes. Analyses used the Kruskal-Wallis procedure. Results showed that male and female athletes differed from each other, and the alpine ski athletes were different in size and composition from the other disciplines. The non-alpine disciplines did not differ.